Generating incomes from dry forest products case studies from Mwinilunga, Kapiri, and Chongwe district, Zambia - Husselman, M. (Stellenbosch University, 2011)
With the increasing demand for forest products due to population growth, urbanization and the opening of global markets, the harvesting and sale of these products has become part of the livelihood strategies of many rural African poor. The low barriers for entry, such as the low cost of production, create the opportunity for very poor households to engage in the trade of many NTFPs. However, the potential of forest based enterprises to contribute to poverty alleviation in African dry forests is not well understood, creating a barrier for effective supporting policies and institutions. This paper presents the findings from a survey conducted in four areas in Zambia. Particular attention is given to the range of products sold by rural households and the opportunities and constraints to participate in this trade. Recommendations to increase returns from forest based enterprises are given.